Effect of hydroalcoholic leaves extract of Datura stramonium on pathogenic Candida albicans: Ali Y. Salman and Mohammed K. Faraj - Salman, Ali Y. (The Iraqi Journal of Veterinary Medicine, 2015)
This research aimed at studying the effect of different concentration of hydroalcoholic leaves extract of Datura stramonium concentration against pathogenic Candida albicans isolated from clinical cases of diarrhea in cows and dogs in Baghdad province. Hydroalcoholic extract of the leaves of Datura stramonium were prepared in different concentrations for In vitro and In vivo study against Candida albicans. In vitro test includes the determination of minimum inhibitory concentration 50, 25, 12.5, 6.25, 3.12 and 1.75mg/1ml), and it was found that the minimum inhibitory concentration was 3.12 mg/1ml. Whereas the in vivo test was performed for the determination of sensitivity test of Candida albicans in concentration of plant 10, 15 and 20 mg/1ml which was compared with same concentration of Nystatin. The study was performed in seven groups of mice according to different concentrations. The infective dose of Candida albicans was 1X108, which was proved by histopathology changes after eight day. The result obtained from invivo study revealed that after the end of the therapeutic period that lasted for 8 days. Confirm the efficacy of Datura stramonium extract at 20% as a treatment for mice infected with Candida albicans.